Preventive Maintenance Scheduling on Belt Conveyor Using Failure Mode Effect and Criticality Analysis - Kristian, Fernado Putra; Mulyono, Julius; Santosa, Hadi (Jurnal Sistem Teknik Industri, 2021)
PT. X is a services and manufacturing company. PT. Y is one of some of industrial companies use the services of PT. X, is one of the biggest chemical fertilizer producer in Southeast Asia. PT Y uses 66 belt-conveyors for distributing the material. In order to arrange maintenance schedule, used preventive maintenance calculations using Failure Mode Effect and Critically Analysis method (FMECA). Preventive maintenance is used to schedule the maintenance of the conveyor beltâ€™s components (belt and primary cleaner). Data analysis obtained a critical belt values are 2.521ð‘¥10âˆ’3 and 1.863ð‘¥10âˆ’3, respectively, on the primary cleaner component. Furthermore, effective maintenance and evaluation time intervals which obtained for belt components is indicating operation time with 92% reliability level or about 215 hours.